Gravity and magneto-telluric study of Manuguru geothermal field, Telangana state, India. (March 2023) - Sakhare, Vishal; Kant, Abhay; Low, Upananda; Biswal, Bishnu P.; Paul, Suman; Hanmanthu, Durgam
Highlights: Characterization of the Manuguru geothermal system of Telangana State, India and identification the deep geothermal reservoir deploying two complementary geophysical surveys viz; gravity and MT. A total of 144 gravity and 27 MT sounding data were acquired covering an area of 200 km 2 . The geophysical study identified several faults acting as conduits for hot water upflow as well as a distinguished low resistivity zone (<4 Ohm-m) at a depth ≥2.4 km indicating deep hot water storage in the area. Abstract: Manuguru geothermal field is located on the southeastern margin of the Godavari River valley. A sequence of rocks of the Gondwana group unconformably lies over a quartzite-phyllite basement of the Pakhal Supergroup in the present study area. A geophysical investigation deploying gravity and magneto-telluric (MT) survey was carried out covering an area of 200 km 2 to characterize the Manuguru geothermal system and locate the probable reservoir source. Bouguer gravity anomaly shows a noticeable variation of 25 mGal ranging from -72 mGal to -47 mGal. Residual gravity and derivative analysis exhibit that there are several basement faults controlling the deep subsurface hot water flow in the area. In the MT study, a total of 27 MT soundings data were acquired at varied frequency ranges (20 kHz to DC). The MT data were analyzed for 1D as well as 2D modeling using the inversion technique to configure the subsurface resistivity distribution along three selected profiles (P1 to P3). Two exploratory drillings conducted based on our studies validate the inferred low resistivity anomalies. To configure basement and fault systems, a 2D forward gravity inversion modeling was performed along a selected profile which showed that the depth of the Archaean basement underlain by the Gondwana and Pakhal sediments ranges from 1.2–2.2 km. The results inferred a 2D resistivity structure with varying resistivity from <2 Ohm-m to >4000 Ohm-m. The study identified a distinguished low resistivity zone (<4 Ohm-m) at a depth ≥2.4 km indicating deep hot water geothermal storage in the area.